2018
DOI: 10.3390/insects9010020
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Extracted Locusta Migratoria Protein Fractions as Value-Added Ingredients

Abstract: Although locusts can be sustainably produced and are nutrient rich, the thought of eating them can be hard to swallow for many consumers. This paper aims to investigate the nutritional composition of Locusta migratoria, including the properties of extracted locust protein, contributing to limited literature and product development opportunities for industry.Locusts sourced from Dunedin, New Zealand, contained a high amount of protein (50.79% dry weight) and fat (34.93%), which contained high amounts of omega-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 35 publications
5
48
2
1
Order By: Relevance
“…e protein content of those grasshoppers was lower than that previously reported in the whole freeze-dried locust and alkali-extracted defatted locusts (65.87 and 82.26% dry weight, respectively) [26]. Clarkson et al [25] reported that crude protein content of L. migratoria was 50.79% (dry weight). e extraction efficiency of WSPP and WSPC were calculated to be 48.77 and 42.86%, indicating high efficacy of protein extraction.…”
Section: Yield and Extraction Efficiencymentioning
confidence: 69%
See 2 more Smart Citations
“…e protein content of those grasshoppers was lower than that previously reported in the whole freeze-dried locust and alkali-extracted defatted locusts (65.87 and 82.26% dry weight, respectively) [26]. Clarkson et al [25] reported that crude protein content of L. migratoria was 50.79% (dry weight). e extraction efficiency of WSPP and WSPC were calculated to be 48.77 and 42.86%, indicating high efficacy of protein extraction.…”
Section: Yield and Extraction Efficiencymentioning
confidence: 69%
“…e yields of the resultant freeze-dried counterparts called WSPP and WSPC were 7.35 ± 0.19 and 7.49 ± 0.19% (wet weight basis), respectively. Clarkson et al [25] found that protein yield in soluble locust fraction from L. migratoria was 9.83%. e difference in extraction yield was probably due to different preparations and extraction procedures.…”
Section: Yield and Extraction Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol extract of L. migratoria has been investigated for its anti-inflammatory effects on BV-2 microglial cells ( Lee et al, 2018 ), inhibitory effect on osteoblast differentiation ( Baek et al, 2019 ), and osteoblastogenic activity ( Baek et al, 2018 ). In addition, the nutritional value of L. migratoria as a novel food has been established ( Clakson et al, 2018 ; Mohamed 2015a ; Mohamed 2015b ). With regard to the nutritional content of L. migratoria , 100 g of dry L. migratoria is comprised of 50.42±2% crude protein, 19.62±0.8% crude fat, 4.78±0.74% carbohydrates, 15.65±1.7% crude fiber, 6.24±0.5% ash, and 3.8±0.2% moisture ( Mohamad, 2015a ).…”
Section: Introductionmentioning
confidence: 99%
“…이외 에도 최근 풀무치의 추출물이 신경모세포 생성 및 조골세포 분화에도 효과가 있는 것으로 나타났다 [8,9]. 또한 풀무치의 영양성분 관련 문헌에 따르면 조단백질 50.42%, 조지방 4.78%, 탄수화물 15.65%, 조섬유 6.24%로 구성되어 있으며 지방산에는 포화지방산(팔미트산, 스테아르산)과 불포화지방 산(올레산, 리놀레산, 오메가-6, 오메가-3 지방산)을 포함하는 것으로 확인되었다 [10][11][12] (Fig. 1, Fig.…”
unclassified